2011
DOI: 10.1074/jbc.m110.173591
|View full text |Cite
|
Sign up to set email alerts
|

The Transmembrane Domain of the Molecular Chaperone Cosmc Directs Its Localization to the Endoplasmic Reticulum

Abstract: The molecular basis for retention of integral membrane proteins in the endoplasmic reticulum (ER) is not well understood. We recently discovered a novel ER molecular chaperone termed Cosmc, which is essential for folding and normal activity of the Golgi enzyme T-synthase. Cosmc, a type II single-pass transmembrane protein, lacks any known ER retrieval/retention motifs. To explore specific ER localization determinants in Cosmc we generated a series of Cosmc mutants along with chimeras of Cosmc with a non-ER res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 69 publications
(68 reference statements)
0
14
0
Order By: Relevance
“…This observation is an indication of the intricate relationship between oligomerization of proteins and their export from the ER. It has been reported that oligomerization of the Cosmc chaperone mediates its retention in the ER (Sun et al, 2011). Here, the BiFC-stable oligomers were retained in the ER while their mCherry counterparts were fully transport-competent.…”
Section: Discussionmentioning
confidence: 65%
“…This observation is an indication of the intricate relationship between oligomerization of proteins and their export from the ER. It has been reported that oligomerization of the Cosmc chaperone mediates its retention in the ER (Sun et al, 2011). Here, the BiFC-stable oligomers were retained in the ER while their mCherry counterparts were fully transport-competent.…”
Section: Discussionmentioning
confidence: 65%
“…COSMC is an ER-localized chaperone specific for the Golgi glycosyltransferase T-synthase and is itself a type II transmembrane protein with homology to the same T-synthase. It resides in the ER due to formation of a homodimer by a disulfide bond within the transmembrane domain that is essential for ER retention (44). Indeed, we observed dimer formation for XXYLT1 (Fig.…”
Section: Discussionmentioning
confidence: 68%
“…Here we used a variety of molecular and biochemical approaches to define key aspects of the molecular basis for the specific recognition of the T-synthase by Cosmc and its role as a regulator of T-synthase folding. Our results demonstrate that Cosmc, an ER resident protein (46), directly binds to a unique hydrophobic region within the N-terminal stem region of T-synthase, which we have termed CBRT. Furthermore, in the absence of Cosmc in cells, the T-synthase cannot fold to become active, and thus any hydrophobic sequences within the T-synthase that might contribute to binding by other chaperones do not assist in correct folding of the enzyme in the absence of Cosmc.…”
Section: Discussionmentioning
confidence: 93%